2015
DOI: 10.2514/1.b35565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Paraffin–Polyethylene Blends as Novel Solid Fuel for Hybrid Rockets

Abstract: A novel paraffin-based blends fuel prepared from pure paraffin wax of the alkane family with polyethylene of the alkene family is proposed and tested in a slab motor to visualize the droplet entrainment mechanism followed by a hybrid rocket motor test to analyze its combustion characteristics. The mechanical strength of the proposed blended fuel is investigated by increasing the polyethylene weight percent. The overall regression rate of 5 wt % of polyethylene with 95 wt % of pure paraffin is found to be 3.9 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 20 publications
3
28
0
10
Order By: Relevance
“…Compared with the pure paraffin, the regression rates of formulation No.1 increased while the regression rates of formulations No.2~No.6 decreased. Since the melting points of formulations doped with the stearic acid were reduced while the liquid viscosities were essentially unchanged, this was beneficial to yield droplets which can promote the mass transfer during combustion process [15]. In contrast, adding AÀC6A, EVA, LDPE, PP and HDPE boosted the liquid viscosities significantly but changed the melting points slightly, thereby the mass transfer was negatively affected due to the increased viscosity can augment the shear force during the droplet detachment [6].…”
Section: The Combustion Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the pure paraffin, the regression rates of formulation No.1 increased while the regression rates of formulations No.2~No.6 decreased. Since the melting points of formulations doped with the stearic acid were reduced while the liquid viscosities were essentially unchanged, this was beneficial to yield droplets which can promote the mass transfer during combustion process [15]. In contrast, adding AÀC6A, EVA, LDPE, PP and HDPE boosted the liquid viscosities significantly but changed the melting points slightly, thereby the mass transfer was negatively affected due to the increased viscosity can augment the shear force during the droplet detachment [6].…”
Section: The Combustion Performancementioning
confidence: 99%
“…Blended additives also can affect the combustion performance of paraffin-based fuel. Kim [15] investigated the combustion characteristics of paraffin-based fuels mixed LDPE, and found that blended LDPE can increase surface tension and melted viscosity leading to a decrease of the amount of fuel droplets during the combustion, thus the regression rate reduced. Kumar [16] fired paraffin grains containing 20 mass % EVA and found that the addition of EVA decreased the regression rate due to the increase of the melting point and viscosity of the melted layer.…”
Section: Introductionmentioning
confidence: 99%
“…A more interesting result is that pure paraffin fuel has displayed a considerable amount of instability in chamber pressure. These low‐frequency pressure oscillations associated with pure paraffin could be attributed to the unstable thin liquid layer formed over the fuel surface during the combustion [32]. These low‐frequency pressure oscillations may be ascribed to the entrainment of liquid fuel droplets from the fuel surface to the combustion zone.…”
Section: Resultsmentioning
confidence: 99%
“…(4) was considered equal to 0.5 (n=0.5). This is a reasonable assumption since the oxidizer mass flux exponent has been observed to range from 0.5 to 0.75 regardless of the type of propellant for most hybrid propulsion systems [1,19,20]. And the time rate of change of the chamber gas volume was neglected because the fuel regression rate is on the order of a few mm/s, much slower than combustion time scales.…”
Section: Linearized Model For Hybrid Rocket Engine Instabilitiesmentioning
confidence: 99%